TREMATODOS DE LAS RANAS DE LA CIENAGA DE LERMA ESTADO DE MEXICO III REDESCRIPCION DE UNA FORMA NORTEAMERICANA DE HAEMATOLOECHUS Y ALGUNAS CONSIDERACIONES SOBRE GLYPTHELMINS CALIFORNIENSIS CORT 1919 - CABALLERO Y C, EDUARDO (Universidad Nacional Autónoma de Mexico, Escuela de Medicina, CD MEXICO, DF, MEX, 1944)
A survey was made of 380 patients (166 ?$, and 214 <?c?) in Guadalajara ranging in age from 5 to 17 yrs The specimens were obtained after a MgSO4 purge and examined either in saline or Lugol's soln The total % of infection for each species was: Trichomo
ANS INST BIOL
Keywords: TREMATODOS, RANAS, CIENAGA DE LERMA, ESTADO DE MEXICO, REDESCRIPCION, FORMA NORTEAMERICANA, HAEMATOLOECHUS, CONSIDERACIONES, GLYP THELMINS CALIFORNIENSIS, CORT, 1919; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; COMPORTAMIENTO ANIMAL